ADOPTION AND UTILIZATION OF EFFECTIVE CONFLICT MANAGEMENT STRATEGIES FOR PROMOTING PEACE-CULTURE IN SECONDARY SCHOOLS IN ANAMBRA STATE, NIGERIA - Ezeugbor Carol O.; Onyali Loyce C.; Okoye Faith O. (European Scientific Journal, ESJ, 2015)
The aim of this study is to investigate Principal’s adoption and utilization of effective conflict management strategies for promoting peaceculture in secondary schools in Anambra State. The study adopted descriptive survey design. Two research questions guided the study and two null hypotheses tested at 0.05 level of significance were formulated for the study. The population of the study consisted of 254 principals and 254 vice principals (Administration) in the public secondary schools of Anambra State. Data were collected using a 22-item questionnaire. The questionnaire was validated by three experts. For the reliability of the instrument, a coefficient value of 0.86 was obtained and was considered satisfactory for the study. Mean and standard deviation were used in answering the research questions. The t-test was adopted in testing the hypotheses at 0.05 level of significance. The findings revealed that principals did not adopt a considerable number of effective conflict management strategies in schools. Also, the extent to which they utilized effective conflict management strategies in building peace-culture was low. It was thus recommended among others, the principals as a matter of urgency should be exposed to the necessity of adopting all the effective conflict management strategies. This should be done through conferences and seminars if the aim of building peace in secondary schools would be achieved.